The terrible hours the man behind the greatest submarine rescue in history - Maas, Peter 1929- (HarperCollins, 1999)
On the eve of World War II, the Squalus, America's newest submarine, plunged to the bottom of the North Atlantic. Miraculously, thirty-three crew members still survived. While their loved ones waited in unbearable tension on shore, their ultimate fate would depend upon one man, U.S. Navy officer Charles "Swede" Momsen -- an extraordinary combination of visionary, scientist, and man of action. In this thrilling true account, prize-winning author Peter Maas vividly re-creates a moment-by-moment account of the disaster and the man at its center. Could he actually pluck those men from a watery grave? Or had all his pioneering work been in vain?